PENCIL DRAWING - FINE ARTS AS A BASIS - Abdurakhimov Lola Khursanovich ,; Alikulova Nodira Ergashevna , (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2023)
Abstract: In this article, pencil drawing as the basis of visual art, realistic depiction of existing things and forms, to develop practical knowledge and skills, as well as aesthetic taste. Love for nature, observation, composition, constructive structure, proportions, perspective, laws of light and shadow are important.